Aerospace-grade compatible surface mounted optical fibre sensor for structural health monitoring of composite structures - Goossens,S; De,Pauw B; Geernaert,T; Salmanpour,MS; Khodaei,ZS; Thienpont,H; Berghmans,F (2018)
We suggest a robust optical fibre sensor package and its installation method for structural health monitoring purposes on carbon fibre reinforced polymer structures with potential to meet aerospace standards.